Can we improve the statistical analysis of stroke trials? Statistical re-analysis of functional outcomes in stroke trials - Bath, Philip M.W. (American Heart Association, 2007)
Background: Most large acute stroke trials have been neutral. Functional outcome is usually analysed using a yes or no answer, e.g. death or dependency vs. independence. We assessed which statistical approaches are most efficient in analysing outcomes from stroke trials.